Aging exacerbates hypertension‐induced cerebral microhemorrhages in mice: role of resveratrol treatment in vasoprotection. Issue 3 (9th February 2015) - Toth, Peter; Tarantini, Stefano; Springo, Zsolt; Tucsek, Zsuzsanna; Gautam, Tripti; Giles, Cory B.; Wren, Jonathan D.; Koller, Akos; Sonntag, William E.; Csiszar, Anna; Ungvari, Zoltan
Summary Recent studies demonstrate that aging exacerbates hypertension‐induced cognitive decline, but the specific age‐related mechanisms remain elusive. Cerebral microhemorrhages (CMHs) are associated with rupture of small intracerebral vessels and are thought to progressively impair neuronal function. To determine whether aging exacerbates hypertension‐induced CMHs young (3 months) and aged (24 months) mice were treated with angiotensin II plus L‐NAME. We found that the same level of hypertension leads to significantly earlier onset and increased incidence of CMHs in aged mice than in young mice, as shown by neurological examination, gait analysis, and histological assessment of CMHs in serial brain sections. Hypertension‐induced cerebrovascular oxidative stress and redox‐sensitive activation of matrix metalloproteinases (MMPs) were increased in aging. Treatment of aged mice with resveratrol significantly attenuated hypertension‐induced oxidative stress, inhibited vascular MMP activation, significantly delayed the onset, and reduced the incidence of CMHs. Collectively, aging promotes CMHs in mice likely by exacerbating hypertension‐induced oxidative stress and MMP activation. Therapeutic strategies that reduce microvascular oxidative stress and MMP activation may be useful for the prevention of CMHs, protecting neurocognitive function in high‐risk elderly patients.